Essentials of genetics - Klug, William S; Ward, Sarah M.; Cummings, Michael R.; Spencer, Charlotte A.; Palladino, Michael A. (Boston : Pearson, 2013)
Known for its focus on conceptual understanding, problem solving, and practical explanations, this text strengthens problem solving coverage and explores the essential genetics content today's students need to know. This edition maintains the book's briefer, less-detailed approach to teaching core concepts. New features of the Eighth Edition include four new Special Topics chapters and thorough updates.
Introduction to genetics -- Mitosis and meiosis -- Mendelian genetics -- Modification of mendelian ratios -- Sex determination and sex chromosomes -- Chromosome mutations: variation in number and arrangement -- Linkage and chromosome mapping in eukaryotes -- Genetic analysis and mapping in bacteria and bacteriophages -- DNA structure and analysis -- DNA replication and recombination -- Chromosome structure and DNA sequence organization -- The genetic code and transcription -- Translation and proteins -- Gene mutation, DNA repair, and transposition -- Regulation of gene expression -- The genetics of cancer -- Recombinant DNA technology -- Genomics, bioinformatics, and proteomics -- Applications and ethics of genetic engineering and biotechnology -- Developmental genetics -- Quantitative genetics and multifactorial traits -- Population and evolutionary genetics -- Conservation genetics.
Brief version of: Concepts of genetics / William S. Klug ... [et al.]. 10th ed. c2012.
Pembekal: Innowawasan Sdn. Bhd, Tel: 03-4042 4998
Includes bibliographical references and index.
Keywords: Genetic Phenomena; Textbooks